Respuesta :

Answer:

Option (2). [tex]2\frac{1}{4}[/tex]

Step-by-step explanation:

The given expression is [[tex]-5\frac{1}{4}-(-7\frac{1}{2})[/tex]]

We can rewrite the fractions as,

[tex]-5\frac{1}{4}[/tex] = [tex]-(5+\frac{1}{4})[/tex]

[tex]-7\frac{1}{2}=-(7+\frac{1}{2})[/tex]

Now we will substitute the fractions in the expression,

[tex][-(5+\frac{1}{4})]-[-(7+\frac{1}{2})][/tex]

= [tex]-(5+\frac{1}{4})+(7+\frac{1}{2})[/tex]

= (-5 + 7) + [tex](-\frac{1}{4}+\frac{1}{2})[/tex]

= 2 + [tex]\frac{2-1}{4}[/tex]

= 2 + [tex]\frac{1}{4}[/tex]

= [tex]2\frac{1}{4}[/tex]

Therefore, Option (2). will be the answer.

ACCESS MORE